2015
DOI: 10.1097/igc.0000000000000440
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Inhibits the Apoptosis of Endometrial Carcinoma Cells Through Activation of the Nuclear Factor κB–inducing Kinase/IκB Kinase Pathway

Abstract: Leptin inhibits EC apoptosis partly through activation of the NIK/IKK pathway in vitro. Ob-Rb overexpression seems to facilitate EC progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 38 publications
(36 reference statements)
2
24
0
Order By: Relevance
“…In their meta-analysis, Wang et al 15 concluded that elevated leptin concentration might constitute an independent risk factor for endometrial cancer. Zhou et al 16 obtained similar results on endometrial cancer cell lines, reporting greater leptin expression in poorly differentiated endometrial cancer cells. In this present study, leptin caused partial inhibition of apoptosis through activation of the NIK/IKK pathway.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In their meta-analysis, Wang et al 15 concluded that elevated leptin concentration might constitute an independent risk factor for endometrial cancer. Zhou et al 16 obtained similar results on endometrial cancer cell lines, reporting greater leptin expression in poorly differentiated endometrial cancer cells. In this present study, leptin caused partial inhibition of apoptosis through activation of the NIK/IKK pathway.…”
Section: Discussionmentioning
confidence: 70%
“…Some studies, for example, the Zhou et al study, report overexpression of leptin receptor Ob-Rb in endometrial cancer. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Several serological studies stated evidences that elevated leptin concentration in serum is correlated with breast cancer risk and counted it as an independent risk factor, in addition to its involvement in many malignancy stages including as cell growth, invasion, migration, metastases, recurrence and therapy response in some organs such as liver [ 17 ], lung [ 18 ], stomach [ 19 ], thyroid [ 20 ], uterus [ 12 ], colon [ 21 ]. A number of investigations were launched to identify the mechanisms which link leptin with tumor growth and progression of breast cancer [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 9 ] Several reports have described leptin role in the proliferation, migration, and invasion of tumor cells and how it prevents apoptosis through different ways. [ 10 14 ] Histologically, many studies have attempted to test the relationship between leptin immunoexpression and clinical parameters in several tumors including colorectal cancer, but the findings are controversial, [ 15 25 ] and yet, not much is known about the clinical significance of leptin phenotype in colorectal carcinomas. Thus, the present study investigates the immunohistochemical staining of leptin in colorectal cancer, and assesses the correlation of its expression with the clinical characteristics and follow up information of these neoplasms.…”
Section: Introductionmentioning
confidence: 99%